37 Shockwave intravascular lithotripsy in calcified coronary lesions: a retrospective, observational, international multi-centre analysis. (17th July 2020) - Aziz, Amir; Khattak, Sophia; Lelasi, Alfonso; Cortese, Bernardo; Testa, Luca; Vigano, Elena; Mokdad, Rami; Pitt, Michael; Basavarajaiah, Sandeep
Abstract : Introduction: Sub-optimal stent expansion due to coronary calcification augments the risk of restenosis and stent thrombosis. Calcium modification is generally achieved by rotational atherectomy or specialized balloons (scoring and cutting balloons), which carries risk of complications. Intravascular lithotripsy (IVL) appears safe and also aids in cracking deep seated adventitial calcium. Although, there are reported studies on this novel technology, there is a lack of real-world data. In this study, we report the experience from 4 centres that undertake high-volume complex coronary interventions. Methods: We enrolled all patients treated with IVL between September 2018 and October 2019 at 4 centres (1 in UK and 3 in Italy). Procedural success and complication were assessed. The clinical outcomes evaluated were; cardiovascular death, target vessel MI (TVMI), target lesion revascularisation (TLR) and MACE (composite of cardiovascular death, TVMI and TLR). Results: During the study period, 100 lesions (in 94 patients) with a mean age of 71±9.7 years (range;30 - 88) were treated using IVL. 70% (n=70) were male, 85% (n=80) had hypertension, 51% (n=48) had diabetes and 20% (n=19) had chronic kidney disease. Acute coronary syndromes accounted for 40% of patients (n=38). De-novo lesions accounted for 66% of cases (n=66) and the remaining 34% (n=34) were restenotic lesions. Left anterior descending artery (56%) accounted for most cases followed by right coronary artery (22%), left circumflex artery (21%), left main (17%) and saphenous vein grafts (3%) procedures. Upfront use of IVL occurred in 18% of cases whilst the rest were bail-out procedures due to inadequate pre-dilatation with conventional balloons. Adjuvant rotational atherectomy (Rota-tripsy) was used in 10 cases (10%) prior to the use of IVL. The mean diameter of IVL balloon was 3.3 ± 0.5mm. Intravascular imaging (IVUS) was used in 19% of cases. Procedural success was achieved in 100% of cases with a complication rate of 2% (2-cases of coronary perforation and one of them resulted in in-hospital mortality). During the median follow-up of 150 days, there were no clinical events including cardiac death, TVMI and TLR. Conclusion: Initial experience and short-term clinical follow-up from IVL use appears safe and effective PCI strategy for dealing with calcified coronary lesions. A high success rate was observed with low event rates and procedural complications. We are enrolling more patients from other centres as part of a larger multi-centre registry and will be able to report this with higher numbers and longer follow-up at BCS 2020. Conflict of Interest: nil